1985
DOI: 10.1038/jcbfm.1985.8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of γ-Hydroxybutyrate on the Relationship between Local Cerebral Glucose Utilization and Local Cerebral Blood Flow in the Rat Brain

Abstract: Summary:The relationship between local cerebral glu cose utilization (LCGU) and local CBF (LCBF) was ex amined during the action of ,(-hydroxybutyrate (GHB) (900 mg/kg i. v.) in conscious rats. GHB induced dis crepant effects on blood flow and metabolism. LCGU was markedly depressed in all structures examined, whereas LCBF was differently affected in that no related changes were observed. Global glucose utilization was markedly depressed ( -51%), whereas global blood flowThe close correlation between metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Our findings of lower levels of functional brain activity following acute baclofen treatment are also in line with previous studies utilizing a different GABA B agonist, γ-hydroxybutyric acid (GHB; Crosby et al, 1983; Kuschinsky et al, 1985). Kuschinsky and colleagues reported lower rates of glucose utilization following acute GHB administration (Kuschinsky et al, 1985), in a similarly distributed network to that reported here following acute baclofen.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings of lower levels of functional brain activity following acute baclofen treatment are also in line with previous studies utilizing a different GABA B agonist, γ-hydroxybutyric acid (GHB; Crosby et al, 1983; Kuschinsky et al, 1985). Kuschinsky and colleagues reported lower rates of glucose utilization following acute GHB administration (Kuschinsky et al, 1985), in a similarly distributed network to that reported here following acute baclofen.…”
Section: Discussionsupporting
confidence: 92%
“…Kuschinsky and colleagues reported lower rates of glucose utilization following acute GHB administration (Kuschinsky et al, 1985), in a similarly distributed network to that reported here following acute baclofen. For example, functional activity in the frontal cortex, caudate, substantia nigra, thalamus and hippocampus was lower in GHB-treated animals, compared to controls.…”
Section: Discussionsupporting
confidence: 75%
“…Specifically in epilepsy, several investigators have shown that the uncoupling of metabolism and perfusion may be an indicator for localizing the seizure origin and sites of propagation (10)(11)(12)(13)(14)(15). This uncoupling was par-ticularly evident in interictal positron emission tomography (PET) images obtained from temporal lobe epilepsy patients (16,17).…”
mentioning
confidence: 99%
“…Specifically in epilepsy, several investigators have shown that the uncoupling of metabolism and perfusion may be an indicator for localizing the seizure origin and sites of propagation (10)(11)(12)(13)(14)(15). This uncoupling was particularly evident in interictal positron emission tomography (PET) images obtained from temporal lobe epilepsy patients (16,17).…”
mentioning
confidence: 99%